Association of Shorter Time to Recurrence and Recurrence-Free Survival with Transthoracic Lung Biopsy in Stage I Lung Cancer - Chae, Kum Ju; Hong, Hyunsook; Park, Hyungin; Yoon, Soon Ho (Cancer research and treatment, 2025)
Purpose We aim to determine whether preoperative percutaneous needle aspiration or biopsy (PCNA/Bx) increases recurrence risk and reduces survival in stage I lung cancer patients, using a nationwide lung cancer registry.Materials and Methods We retrospectively included 3,452 patients diagnosed with stage I lung cancer who underwent curative surgery between 2014 and 2019, as recorded in the Korean Association of Lung Cancer Registry. To balance the characteristics of patients with and without PCNA/Bx, we applied inverse probability of treatment weighting. We used cumulative incidence plots and a weighted subdistribution hazard model to analyze time to recurrence. Recurrence-free survival and overall survival were analyzed using Kaplan-Meier curves and weighted Cox proportional hazard ratio models.Results In patients with adenocarcinoma, the use of PCNA/Bx was associated with a 1.9-fold increase (95% confidence interval [CI], 1.5 to 2.4) in the risk of recurrence and a 1.7-fold decrease (95% CI, 1.3 to 2.2) in recurrence-free survival. Subgroup analysis based on pathologic pleural invasion revealed that the risk of recurrence increased when PCNA/Bx was performed, with 2.1-fold (95% CI, 1.5 to 2.8) in patients without pleural invasion and 1.6-fold (95% CI, 1.0 to 2.4) in those with pleural invasion. No association was found between the use of PCNA/Bx and overall survival.Conclusion Preoperative PCNA/Bx was associated with increased recurrence risks in stage I adenocarcinoma, regardless of pathologic pleural invasion status. In early lung cancer cases where adenocarcinoma is strongly suspected and curative surgery is feasible, the use of transthoracic biopsy should be approached with caution.